Territorial Approach to Spatial Dynamics Based on Posuo and Kawia Tradition of the Labalawa Community of Baubau City - Mimin Trianus; Lisa Dwi Wulandari; Ema Yunita Titisari (Budapest International Research and Critics University, 2022)
This study aims to identify and analyze space territories in the kawia traditions of the Labalawa community. The method used in this research is descriptive qualitative by analyzing the results of the identification of the formation of territory based on changes in shape, size, boundaries, and space components, sampling was carried out by purposive sampling with the criteria of house types of Banua tada and stone houses and differences in the availability of space on the object of observation. The results showed that the space territory was dominated by semi-fixed elements and non-fixed elements, changes in the function of space during the posuo and kawia tradition from day to day were more dominated by public functions, and the condition of adding space called kaompu with the stage form was more influenced by factors availability of open space and also because of the tradition of building the Labalawa community which is practiced from generation to generation through the posuo and kawia tradition.